Laparoscopic splenectomy: case series of 24 patients - Shakya, Vikal Chandra; Paudyal, Bishesh (Journal of Society of Surgeons of Nepal, 2016)
Introduction and Objective: Splenectomy has mostly been performed by open surgery. Laparoscopy seems to be a meaningful alternative to open technique.Materials and Methods: This study was done in patients presenting to hematology and surgery department of Civil Service Hospital who underwent laparoscopic splenectomy from January 2013 to November 2015Results: There were 24 patients (16 females, 8 males). The diagnoses were idiopathic thrombocytopenic purpura in 19, hereditary spherocytosis in 2, @hemolytic anemia in 2, b-hemolytic anemia in 1. The mean operative time was 130+49 minutes. The mean postoperative stay was 5+2.11 days. Laparoscopic splenectomy could be completed in 21 patients. Rest 3 needed conversion to open (causes being excessive bleeding form splenic vein, splenic tear, and excessively low platelet counts). Three patients needed additional pfanneinsteil/lumbar incision to retrieve the spleen.Conclusion: Laparoscopic splenectomy could be successfully contemplated in patients with hematological diseases, more so if spleen is of normal or mildly enlarged; and could be an advantageous alternative to open splenectomy.